Numerical simulation of cold forging process to investigate folding defect in enclosed dies - Payman Abhari (Mechanics and Advanced Technologies)
In the precision forging industries, improving product quality and reducing product cost are important cases. Enclosed-die forging is one of the precision forging processes. In this paper, the cold forging process in the enclosed dies by using kinematical mechanism to create precision parts is considered. The numerical simulation techniques by using the rigid-plastic finite element method (FEM) as software QForm 2D have been applied to investigate defect as a folding defect in this paper. Based on the finite element simulations, forming characteristics such as deformation patterns (gridlines distortion), distributions of effective strain and stress at several stages of process as single-ended and double-ended with different forming parameters to avoid folding defect in cold forging process have been investigated. The lower die velocity vs. geometric ratio by using this numerical simulation method has been determined.